Pathogenesis, patomorphological features and histologic differential diagnostics of primary, recurrent and secondary aneurysmal bone cysts in children and teenagers - V. V. Grigorovsky; Yu. N. Guk; A. V. Roslavtsev (Zaporozhye State Medical University, 2012)
The purpose of this study was the following: on the basis of the analysis of own biopsy-histologic material to establish the features of pathomorphologic changes which are observed in the lesion foci of primary, recurrent and secondary aneurysmal bone cysts (ABC) in children and teenagers and which are the basis of their differential histologic diagnosis. АBC passes cyclic development that is the progressing stage which is characterized by high resorptive-proliferative activity and increase of volume focus, the stabilization stage when the focus volume increase stops, and the regression stage when fi brosing and ossifi cation of capsular-septal structures prevail, including osteosclerosis, with remodelling of bone elements and some decrease of focus dimensions. Some part of total number of all АBC make up secondary hemorrhagic cysts which arise in the foci of a pathologic tissue in other tumours and tumorlike lesions of bones. An incomplete removal of pathologic tissue of ABC with properties of high resorptive activity with respect to the adjacent bone tissue should be considered the main reason of ABC-reccurence after surgical treatment.